2020
DOI: 10.1097/shk.0000000000001681
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Derived Mitochondrial Transplantation Reduces Inflammation, Enhances Bacterial Clearance, and Improves Survival in Sepsis

Abstract: Background: Mitochondrial transplantation is a promising strategy for the treatment of several diseases. However, the effects of mitochondrial transplantation on the outcome of polymicrobial sepsis remain unclear. Methods: The distribution of transplanted mitochondria in cecal ligation and puncture (CLP)-operated mice was detected at 2 and 12 h after intravenous injection in the tail (n ¼ 3). Then, the effects of mitochondrial transplantation on bacterial clearance (n ¼ 7), systemic inflammation (n ¼ 10), orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…neurological tissue [8], liver [9], and limb [10], as well as in sepsis [11]. Most astonishingly, the clinical trials of MT has also been reported by McCully's group in pediatric patients with cardiogenic shock following ischemia-reperfusion injury in 2017 [12] and 2020 [13].…”
Section: Introductionmentioning
confidence: 91%
“…neurological tissue [8], liver [9], and limb [10], as well as in sepsis [11]. Most astonishingly, the clinical trials of MT has also been reported by McCully's group in pediatric patients with cardiogenic shock following ischemia-reperfusion injury in 2017 [12] and 2020 [13].…”
Section: Introductionmentioning
confidence: 91%
“…Based on the fact that elimination of dysfunctional mitochondria and production of healthy mitochondria improve the recovery of organ function in sepsis [ 9 ], application of mitochondrial transplantation can be considered as a promising treatment opportunity to improve sepsis-related organ dysfunction. Given that few studies have evaluated the effects of mitochondrial transplantation in sepsis-related organ dysfunction [ 18 20 ], it is important to perform extensive studies in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical reports have demonstrated an incontrovertible efficacy signal associated with MT in multiple organ systems, including heart, lung, neurological tissue, liver, and kidney, as well as in sepsis. [3][4][5][6][7] It will be fascinating to determine the many unsolved scientific questions concerning MT, such as the precise mechanism of action, the optimal routes and methods of administration, and the specificity of disease indications such as the beneficial ventricular remodeling effects already shown by the Boston group. 8 The universal benefits of improved mitochondrial function include increased adenosine triphosphate generation, mitigation of free radical stress, augmented mitochondrial biogenesis, improved metabolism, cytoprotective signaling properties, and anti-inflammation.…”
mentioning
confidence: 99%
“…8 The universal benefits of improved mitochondrial function include increased adenosine triphosphate generation, mitigation of free radical stress, augmented mitochondrial biogenesis, improved metabolism, cytoprotective signaling properties, and anti-inflammation. Transplantation of respiration-competent allogenic mitochondria reduced multiorgan dysfunction in a rat sepsis model in part via attenuation of the inflammatory cytokine response, 7 suggesting the theoretical value of preemptive, systemically administered MT trial designs for extracorporeal membrane oxygenation indications.…”
mentioning
confidence: 99%